Restricted Replication of the Live Attenuated Influenza A Virus Vaccine during Infection of Primary Differentiated Human Nasal Epithelial Cells - Fischer, William A. (Vaccine, 2015)
Live Attenuated Influenza Vaccine (LAIV) strains are associated with cold adapted, temperature sensitive and attenuated phenotypes that have been studied in non-human or immortalized cell cultures as well as in animal models. Using a primary, differentiated human nasal epithelial cell (hNEC) culture system we compared the replication kinetics, levels of cell-associated viral proteins and virus particle release during infection with LAIV or the corresponding wild type (WT) influenza viruses. At both 33°C and 37°C, seasonal influenza virus and an antigenically matched LAIV replicated to similar titers in MDCK cells but seasonal influenza virus replicated to higher titers than LAIV in hNEC cultures, suggesting a greater restriction of LAIV replication in hNEC cultures. Despite the disparity in infectious virus production, the supernatants from H1N1 and LAIV infected hNEC cultures had equivalent amounts of viral proteins and hemagglutination titers, suggesting the formation of non-infectious virus particles by LAIV in hNEC cultures.